Implementasi Pemupukan Berdasarkan Analisis Sensor Tanah berbasis IoT untuk Optimalisasi Pertumbuhan Tanaman Jagung (Zea mays L.) - Moh Hasbi Ash Shidiqi; Eka Nurmala Sari; Aldy Bahaduri Indraloka; Bagus Eka Mahendra; Zuyinatul Magfiroh (BPFP Universitas Bengkulu, 2026)
[OPTIMIZING CORN (Zea mays L.) GROWTH THROUGH FERTILIZATION BASED ON IOT SOIL SENSOR ANALYSIS. Corn (Zea mays L.) plays an important role in Indonesia's agricultural sector as a source of food, animal feed, and industrial raw materials. However, the main challenge in cultivation is improper fertilization, which can reduce yields and damage the environment. Efficient and sustainable fertilization is necessary to increase productivity. Internet of Things (IoT)-based soil sensor technology provides a solution by providing accurate data on soil conditions that help with fertilization efficiency. The purpose of this study was to examine the effect of fertilization variations adjusted to the results of IoT-based soil sensor analysis on corn plant growth. The study was conducted in Labanasem Village, Banyuwangi Regency, from July to September 2025, using a non-factorial randomized block design (RBD) with four treatments, namely conventional, chemical, balanced, and organic fertilization, repeated six times. Data were collected using IoT soil sensors to analyze pH, moisture, temperature, and nutrients. Fertilization was carried out at 20, 35, and 55 days after planting for conventional and chemical fertilizers, while balanced and organic fertilizers followed the dosage recommendations from the IoT system. The results showed that balanced fertilization did not differ significantly from conventional and chemical fertilization in terms of plant growth parameters, including plant height, number of leaves, stem diameter, leaf area, leaf area index, and flowering age (p > 0.05). Organic fertilization showed significantly different results (p < 0.05), but balanced fertilization was more efficient in reducing input costs and supporting agricultural sustainability compared to organic fertilization, as well as supporting agricultural sustainability. IoT-based soil sensor technology can improve fertilization precision and support fertilizer use efficiency.based soil sensors and balanced fertilization is recommended to increase corn production efficiently and sustainably.